Psychiatric morbidity in newly diagnosed carcinoma cervix and its comparison with benign condition - Raj, Rajnish; Bhagat, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study the psychiatric morbidity among newly diagnosed carcinoma cervix and its comparison with benign gynaecological diseases of cervix. Cervical cancer is the second most common cancer in the world and ranked first in India. It is mainly caused by sexually transmitted infection (STI) of human papilloma virus (HPV). Methods: It was an open labeled, cross-sectional and extended phase study that screened 158 patients in the age group of 18-70 years who fulfilled both inclusion and exclusion criteria and screened positive on liquid based cytology (LBC), as per guidelines of Bathesda system in Government Medical College, Patiala. 13 patients dropped out of study and finally 145 patients were enrolled. They were further divided after biopsy into two groups as per histopathological examination (HPE) i.e., Group-1, N=47 women HPE positive for cervical intraepithelial neoplasia (CIN) as Cases and Group-2, N=98 HPE negative as Control Hospital Anxiety Depression Scale (HADS) was used to screen psychiatric morbidity for depression and anxiety. Whereas, severity was assessed on Hamilton Rating Scale for Depression (HAM-D) and Hamilton Rating Scale for Anxiety (HAM-A). Results: Mean age of Group-1 was 38.45±11.22 SD years and Group-2 was 36.67±8.54 SD years. Psychiatric morbidity in Group-1 was 65.95% whereas Group-2 was 21.42%. P value obtained on comparing HADS score of two groups was significant (p <0.050). After active intervention there was a significant reduction in psychiatric morbidity of two groups (72% in Group-1 and 81.3% in Group-2). Conclusions: The study revealed that the breaking of bad news has a significant psycho-social impact on patients suffering from carcinoma cervix than benign group.